Numerical Investigation of Constructal Distributors with Different Configurations - 范志伟 周兴贵 罗灵爱 袁渭康 (Chinese journal of chemical engineering, 2009)
Seven distributors with different configurations are designed and optimized by constructal approach. Their flow distribution performance and energy dissipation are investigated and compared by computational fluid dynamics （CFD） simulation. The reliability of CFD simulation is verified by experiments on the distributor that has all distributing rectangle channels on a plate. The results show that the symmetry of the distributing channels has decisive influence on the performance of flow distribution. Increasing the generations of channel branching will improve the flow distribution uniformity, but on the other hand increase the energy dissipation. Among all the seven constructal distributors, the distributor that has dichotomy configuration, Y-type junctions and straight interconnecting channels, is recommended for its better flow distribution performance and less energy dissipation.